PENGARUH KINERJA KEUANGAN, KEPUTUSAN INVESTASI DAN PERTUMBUHAN LABA TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Gustomo Rizqi Baehaqi; Tsarina Zenabia (Paulus Journal of Accounting (PJA), 2026)
This study aims to examine the effect of financial performance, investment decisions, and profit growth on firm value, with dividend policy as a moderating variable, in food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The population in this study was all food and beverage companies listed on the IDX for the 2020-2024 period. This study used a purposive sampling technique, resulting in a sample size of 18 companies with a five-year observation period, resulting in 90 data points. The data used were secondary, and eViews 9 was used as a statistical test tool. The results indicate that financial performance and investment decisions have a partial positive effect on firm value, while profit growth has no effect. Dividend policy moderates the effect of financial performance and investment decisions, but does not moderate profit growth on firm value. The results simultaneously indicate that financial performance, investment decisions, profit growth, and dividend policy simultaneously influence firm value.